Quality Management of Indonesian Education Services in the Digital Era: A Systematic Literature Review - Basri Asyibli; Abdul Malik Romadhon; Anis Zohriah; Abdul Muin (Didaktika: Jurnal Kependidikan, 2025)
This research aims to analyze the quality of educational services in Indonesia in the digital era by highlighting the application of the SERVQUAL dimension in digital education quality management. The research method used is a systematic literature review based on the PRISMA protocol, by identifying and synthesizing 21 scientific articles published in 2020–2025 that are relevant and indexed nationally and internationally. The results of the study revealed that the use of digital technology contributes significantly to improving accessibility, administrative efficiency, and learning flexibility; However, service gaps are still found in the aspects of reliability and tangibles due to limited infrastructure and digital literacy. On the other hand, the dimensions of responsiveness, assurance, and empathy can be strengthened through educator training, strengthening digital governance, and providing personalized technology-based services. The implications of this study emphasize the importance of continuous innovation, data-driven quality measurement, and multi-stakeholder collaboration so that educational institutions are able to meet students' expectations and increase competitiveness; meanwhile, further research is suggested to highlight the personalization of AI-based services and the effectiveness of digital evaluation models across educational levels.